Актуальність урахування впливу показників якості напруги при обліку електричної енергії - Шевченко, Сергій Юрійович; Волохін, В. В.; Дяговченко, І. М.; Макуха, Д. М. (НТУ ХПІ", 2015)
Розглянуто і проаналізовано влив на роботу приладів обліку електричної енергії показників якості напруги, зокрема відхилення напруги від нормованих значень, коливання напруги, несинусоїдальність напруги, несиметрія напруги, провали напруги, імпульси напруги та тимчасові перенапруги. Визначено основні причини виникнення таких відхилень якості електроенергії, зроблено висновки що до їх впливу на прилади обліку електричної енергії, розглянуто основні методи їх врахування.

The eltctricity meters used in electric distribution networks are based on a conventional definition of active and reactive energy (or power) for sinusoidal voltages and currents, containing only the fundamental frequency component. Today there is not enough attention payed to the problems of voltage quality distortions. Meanwhile different deviations of voltage in electric grids can lead inaccuracies in power accounting. As a consequence, the performances of energy meters in the presence are need to be improved. Espesually it is actual for such quality indicatirs as voltage deviation from standard values, voltage fluctuations, the nonsinusoidal voltage, voltage unbalance, voltage dips, voltage pulses and temporary overvoltages. In this work it is made the analysis of these factors, considered their influences on electric meters work and mentioned the main sources of such distortions. Also the methods of voltage deviations considering are determined.
The relevance of voltage quality considering in electrical energy accounting
Keywords: прилади обліку; лічильники електроенергії; відхилення напруги; похибка обчислення енергії; тимчасові перенапруги; electricity meter; electric energy; voltage; deviation; influence